Etika Hidup Bermasyarakat. Analisis Terhadap De Civitate Dei Karya St. Agustinus - C.B. Mulyatno (Jurnal Orientasi Baru, 2008)
To help build a peaceful society that respects justice and personal dignity, we need a solid ethical foundation. For St. Augustine, ethical norms are inseparable from human conscience. From the depth of one's heart, the power of life flows. Each individual has an interior drive that leads him or her to the ultimate goal of life, which is a perfect happiness. Building a good and civilized society is a shared responsibility. Each individual is called to participate in it and within that social atmosphere each person is challenged to move forward in pursuing a perfect happiness and everlasting peace.